Science of weather, climate and ocean extremes - Hay, John E. 1943- (Developments in weathers and climate science, 2023)
"Science of Weather, Climate and Ocean Extremes presents an evidence-based view of the most important ways in which the build-up of greenhouse gases in the atmosphere is affecting both our atmosphere and the oceans. The book provides compelling reasons why concerted action is required to slow the rate at which the atmosphere and oceans are changing. It not only covers longer-term changes in extremes and their causes, but also considers the drivers and attribution of extreme events, including relevant methods and techniques." --Amazon.